2006
DOI: 10.1021/la060797t
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Alkenes with Hydrogen-Terminated and Photooxidized Silicon Surfaces. A Comparison of Thermal and Photochemical Processes

Abstract: Reagentless micropatterning of hydrogen-terminated Si(111) via UV irradiation through a photomask has proven to be a convenient strategy for the preparation of ordered bicomponent monolayers. The success of this technique relies upon the differential rate of reaction of an alkene with the hydrogen-terminated and photooxidized regions of the surface. Monolayer formation can be accomplished under either thermal or photochemical conditions. It was observed that, after 3 h, reaction in neat alkene solution irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 32 publications
8
52
1
4
Order By: Relevance
“…24, 32 We recently reported on the reaction of oxidized silicon surfaces with alkenes, observing signals in the X-ray photoemission spectrum corresponding to oxidized hydrocarbon. 27 In this study the thermal reaction of 1-decene with oxidized silicon surfaces was found to be consistent with Markovnikoff addition of the alkene to the silanol at lower temperature (80°Ca n d∼35°C in the Rayonet photoreactor) and antiMarkovnikoff at higher temperature (150°C). The X-ray photoemission spectrum of the high-temperature reaction showed evidence for the presence of carboxylic acid groups, indicating that the organic material had been oxidized.…”
Section: Resultssupporting
confidence: 71%
“…24, 32 We recently reported on the reaction of oxidized silicon surfaces with alkenes, observing signals in the X-ray photoemission spectrum corresponding to oxidized hydrocarbon. 27 In this study the thermal reaction of 1-decene with oxidized silicon surfaces was found to be consistent with Markovnikoff addition of the alkene to the silanol at lower temperature (80°Ca n d∼35°C in the Rayonet photoreactor) and antiMarkovnikoff at higher temperature (150°C). The X-ray photoemission spectrum of the high-temperature reaction showed evidence for the presence of carboxylic acid groups, indicating that the organic material had been oxidized.…”
Section: Resultssupporting
confidence: 71%
“…The mechanism was further delineated by studying the wavelength dependence of this photochemical reaction. It had been reported before by Wayner and co‐workers that 300 nm irradiation of SiO x in the presence of 1‐decene yielded a static water contact angle of 59° 135. Irradiation with wavelengths greater than 275 nm of fused silica in the presence of 1‐hexadecene also yielded only 60°.…”
Section: Alkenes and Alkynesmentioning
confidence: 80%
“…Cycloaddition [139][140][141][142][143] Condensation [144,145] Silanization with chlorosilanes and trichlorosilanes with azanes [146][147][148] Arylation [149] Hydrosilation [138,[150][151][152][153][154] Phosphonation [155][156][157] Reaction with metal organic reagents/Grignard route [158][159][160] Electrochemical deposition See Figure 5 in section 1.3 of this review [161,162] Brought to you by | University of New Orleans Authenticated Download Date | 5/29/15 4:06 PM for the study of monolayers. In 1917 Irving Langmuir [166] developed the theoretical and experimental fundamentals that lead to the birth of a new method for the fabrication of ordered monomolecular films on a liquid surface, which are also known as Langmuir films.…”
Section: Reaction Referencementioning
confidence: 99%